Species and Region-wise Mushroom Production in Leading Mushroom Producing Countries - China, Japan, USA, Canada and India - Singh, Manjit; Kamal, Shwet; Sharma, Ved Parkash (Mushroom Research, 2021)
There has been rapid growth in mushroom production  worldwide reaching 43 million tonne in 2018-19. The subsequent two years have been a difficult period for all economies of the world as COVID-19 has impacted all the sectors including mushroom output. Despite the rapid increase in mushroom production in this century, the production is highly localized.  In all major mushroom producing countries, there are specific regions of concentrated production.  In countries producing different types of mushrooms such as China, Japan and India, there are localized regions of production for different species. Species and  region-wise production in major mushroom producing countries has been presented here for 2018-19. These data may serve as a bench mark to analyse the changes in mushroom production in the post-COVID era.